\(a^3+b^3+c^3=3bac\)
=>\(\left(a+b\right)^3-3ab\left(a+b\right)+c^3-3abc=0\)
=>\(\left[\left(a+b\right)^3+c^3\right]-3ba\left(a+b+c\right)=0\)
=>\(\left(a+b+c\right)\left[\left(a+b\right)^2-c\left(a+b\right)+c^2\right]-3ab\left(a+b+c\right)=0\)
=>\(\left(a+b+c\right)\left(a^2+2ab+b^2-ac-bc+c^2-3ab\right)=0\)
=>\(a^2+b^2+c^2-ab-ac-bc=0\)
=>\(2a^2+2b^2+2c^2-2ab-2ac-2bc=0\)
=>\(\left(a^2-2ab+b^2\right)+\left(b^2-2bc+c^2\right)+\left(a^2-2ac+c^2\right)=0\)
=>\(\left(a-b\right)^2+\left(b-c\right)^2+\left(a-c\right)^2=0\)
=>a=b=c
\(a^3+b^3+c^3=3abc\\\Rightarrow a^3+b^3+c^3-3abc=0\\\Rightarrow(a+b)^3+c^3-3ab(a+b)-3abc=0\\\Rightarrow (a+b+c)^3-3(a+b)c(a+b+c)-3ab(a+b+c)=0\\\Rightarrow(a+b+c)[(a+b+c)^2-3(a+b)c-3ab]=0\\\Rightarrow(a+b+c)(a^2+b^2+c^2+2ab+2bc+2ca-3ac-3bc-3ab)=0\\\Rightarrow(a+b+c)(a^2+b^2+c^2-ab-bc-ca)=0\\\Rightarrow a^2+b^2+c^2-ab-bc-ca=0(vì.a+b+c\ne0)\\\Rightarrow2a^2+2b^2+2c^2-2ab-2bc-2ca=0\\\Rightarrow(a^2-2ab+b^2)+(b^2-2bc+c^2)+(c^2-2ca+a^2)=0\\\Rightarrow(a-b)^2+(b-c)^2+(c-a)^2=0\)
Ta thấy: \(\left\{{}\begin{matrix}\left(a-b\right)^2\ge0\forall a,b\\\left(b-c\right)^2\ge0\forall b,c\\\left(c-a\right)^2\ge0\forall a,c\end{matrix}\right.\)
\(\Rightarrow\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2\ge0\forall a,b,c\)
Mà: \(\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2=0\)
nên: \(\left\{{}\begin{matrix}a-b=0\\b-c=0\\c-a=0\end{matrix}\right.\Rightarrow a=b=c\)
Vậy: ...
\(---\)
Các HĐT được sử dụng trong bài:
\(a^3+b^3=\left(a+b\right)^3-3ab\left(a+b\right)\)
\(\left(a+b+c\right)^2=a^2+b^2+c^2+2ab+2bc+2ca\)
$\text{#}Toru$